Impact of School Tobacco-Free Policy and Tobacco Risk Education on Youth Cigarette and E-Cigarette Use - Vahe Heboyan; Bruce Riggs (Georgia Southern University, 2020)
Background: Smoking rates have declined over the last half-century, however, e-cigarette use has more than tripled in the recent years. Tobacco-risk education and tobacco-free policies are critical policy instruments to help prevent youth tobacco use. This study evaluates the impact of these policies on youth cigarette and e-cigarette use. Methods: Data from the 2013/2015 Georgia Youth Tobacco Survey (GYTS) is used to test for statistical differences in tobacco use status across school-based tobacco control policies and estimate their impact on cigarette and e-cigarette use. Data includes 5,285 participants representing 2013 middle school (n=2,099), 2013 high school (n=1,775), and 2015 high school (n=1,411). Current cigarette and e-cigarette use is measured as having used them in the past month. Students were asked if their school has a tobacco-free policy and if they were taught in classes about why they should not use tobacco. Multivariate logistic regression and Chi-squared tests are used to analyze data. Results: The use of cigarettes among high school students has decreased, however the use of e-cigarettes has increased. Strong statistical associations exist between tobacco-use behavior and tobacco-control policies, however, these associations were not consistent across all cohorts. Smoking disparities exist where males, White and Hispanic students smoked at much higher rates. Conclusions: The rise of e-cigarette popularity may have significant health effects and become a gateway to smoking cigarettes. The positive impact of tobacco-free policies on youth cigarette use is counter-intuitive and may be the result of adoption of tobacco-free policies by the schools where tobacco use is of a significant concern, hence, higher smoking rates. Future research should examine the effects of these policies, their enforcement, and length of existence in detail to provide more evidence into the effectiveness of these policies.